Kualitas Laporan Keuangan UMKM Berkaitan Dengan Pelatihan Akuntansi, Skala Usaha, Pemanfatan Informasi Akuntansi - Endang Purwanti; Rafli Hendrawan Mustofa (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Accounting inability is one of the main factors that cause problems and result in the failure of small and medium-sized companies in developing their businesses. This study aims to examine the effect of accounting training, business scale and the use of accounting information on the quality of financial reports (a case study at the UMKM Tingkir Village Salatiga). Methods of data analysis using validity test, reliability test, multiple regression analysis, hypothesis testing. Hypothesis testing uses the T test, F test and coefficient of determination to test the effect of accounting training, business scale and the use of accounting information on the quality of financial reports at UMKM in Tingkir Village, Salatiga. The results showed that Accounting Training and Business Scale had a significant effect on the Quality of Financial Statement Presentation. The use of information has no significant effect on the quality of the presentation of financial statements